The effect on staff perceptions of online learning when using a non-traditional approach to staff development - Simpson, Vicki (Proceedings of the International Conference on Networked Learning, 2002)
Staff development plays a crucial role in the adoption of new technology. However, the appropriate requirements for effective staff development in terms of emphasis, content and delivery are often not met. This paper identifies the key factors identified within current research and proposes a course methodology and design that addresses these issues. The evaluation focuses on the success of the methodology and the role of the individual participant’s pedagogical style with regard to the adoption of new technology. The paper concludes that while a traditional didactic pedagogical approach (in both the individual participant and in the design of staff development courses) may not affect uptake, it may result in inappropriate adoption.